Mirzam C. Pérez, The Comedia of Virginity: Mary and the Politics of Seventeenth-Century Spanish Theater - Natalia Fernández (Universitat Autònoma de Barcelona, 2016)
Reseña de Mirzam C. Pérez, The Comedia of Virginity: Mary and the Politics of Seventeenth-Century Spanish Theater, Waco (Texas), Baylor University Press, 2012, 173 pp. ISBN: 9781602586451.